Determinants of consumer’s purchasing behavior towards online food delivery services - Md Jusoh, Zuroni; Saworo, Siti Norizazi Wanani; Rahiman, Nurnazrenatasah; Zainudin, Norzalina (Human Resource Management Academic Research Society, 2022)
This study aimed to examine the determinants of consumer purchasing behavior towards online food delivery services in Peninsular Malaysia. There were 384 respondents involved in this study from states that are Selangor, Johor, Pulau Pinang, and Terengganu through multi-stage cluster sampling and convenience sampling. The data were collected through a questionnaire. This study uses descriptive analysis and Multiple Linear Regression analysis. Multiple Linear Regression analysis found three significant factors: perceived usefulness, attitude, and behavioral intention. These demonstrate as much as 59.2% of the variance in consumer purchasing behavior towards online food delivery services in Peninsular Malaysia is obtained from the influence of attitude, perceived usefulness, and behavioral intention studied, and the attitude factor is the most influence factor influencing consumer’s purchasing behavior towards online food delivery services (?=0.367, p?0.001). In conclusion, attitude, perceived usefulness, and behavioral intention are the determinants of consumer purchasing behavior towards online food delivery services. Therefore, in line with the study's findings, governments and stakeholders need to play important roles in increasing perceived usefulness, attitude, and purchasing intention. Further studies can be expanded to other states in Malaysia to form a larger sample size representing the whole of Malaysia for bias avoidance.